Death in Banaras - Parry, Jonathan P. (The Lewis Henry Morgan lectures, 1994)
As a place to die, to dispose of the physical remains of the deceased and to perform the rites which ensure that the departed attains a 'good state' after death, the north Indian city of Banaras attracts pilgrims and mourners from all over the Hindu world. This book is primarily about the priests and other kinds of 'sacred specialist' who serve them: about the way in which they organise their business, and about their representations of death and understanding of the rituals over which they preside.